2020
DOI: 10.1101/2020.04.14.20065318
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

State-level variation of initial COVID-19 dynamics in the United States: The role of local government interventions

Abstract: During an epidemic, metrics such as R 0 , doubling time, and case fatality rates are important in understanding and predicting the course of an epidemic. However, if collected over country or regional scales, these metrics hide important smaller-scale, local dynamics. We examine how commonly used epidemiological metrics differ for each individual state within the United States during the initial COVID-19 outbreak. We found that the case number, and trajectory of cases, differs considerably between states. We s… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 21 publications
0
15
0
Order By: Relevance
“…Compared with state-level US literature, we found less provincial-and territorial-level variation in NPI implementation in Canada. 13,14 In Canada, we consistently found that school closures were among the first NPIs implemented at the…”
Section: Date Of Npi Implementationmentioning
confidence: 97%
“…Compared with state-level US literature, we found less provincial-and territorial-level variation in NPI implementation in Canada. 13,14 In Canada, we consistently found that school closures were among the first NPIs implemented at the…”
Section: Date Of Npi Implementationmentioning
confidence: 97%
“…Additionally, while data are collected within local medical facilities during an emerging pandemic, outbreak rates are typically reported at aggregate levels. 4 In this article, we show the necessity of analyses on a lower level. This paper proceeds as follows.…”
mentioning
confidence: 90%
“…Non-pharmaceutical interventions have therefore been implemented to ameliorate the tidal wave at the peak of the epidemic (the so-called flattening of the curve) [5][6][7] . While national or international measures such as border closures, socialdistancing, lock-downs, and furloughs have their merit in slowing the epidemic 8,9 , they also interrupt global supply chains and may thus starve health care systems from necessary equipment 10 .…”
Section: Introductionmentioning
confidence: 99%